Dukungan Kelularga dan Kemandirian Pasien Setelah Kateterisasi Jantung: Studi Cross-Sectional - Indah Wulandari; Shafira Alief Ramadhaniyar (Faletehan Health Journal, 2026)
Cardiac catheterization is a common invasive procedure for diagnosing and treating coronary heart disease. Post-procedural independence is essential to support optimal recovery and prevent complications. Family support plays a critical role in facilitating self-care, motivation, and functional independence among patients after cardiac catheterization. This study aimed to examine the relationship between family support, age, sex, and patient independence after cardiac catheterization at the Cardiology Outpatient Clinic of Dr. Dradjat Prawiranegara Hospital, Serang, Indonesia. A cross-sectional design with 32 participants was used. Family Support Scale (FSS) and Lawton Instrumental Activities of Daily Living (IADL) were employed to measure family support and independence. Data were analyzed using Chi-square. The results showed that 62.5% of patients had high family support and 56.2% were independent. A significant association was found between family support and independence (p = 0.021), while age (p = 0.317) and sex (p = 0.442) showed no significant relationship. These findings highlight the importance of integrating family-centered care into post-catheterization rehabilitation.